The Perception Of Red Chili Farmers On The Implementation Of Pt. Inalum's Csr (Coorporate Social Responbility) Program In The Village Of Lubuk Cuik Distric Of Lima Puluh, Batu Bara Regency) - Sasmita Siregar; Yudha Andriansyah; Khairunnisa Rangkuti (JASc (Journal of Agribusiness Sciences), 2021)
This study aims to analyze how the perception of red chilli farmers about capital loan programs and infrastructure improvements from PT Inalum and to analyze how the perception of red chilli farmers about Saprodi assistance programs in the form of red chilli seeds, mulch, pesticides, and electric spraying in Lubuk Cuik village This research uses descriptive analysis method by looking at the perception of red chilli farmers in Lubuk Cuik Village regarding CSR (Corporate Social Responsibility) program from PT Inalum in the form of a capital loan program for the Rice Field Infrastructure Improvement Program and a production input assistance program in the form of: red chili seeds, Mulch, Pesticides , Electric spriyng Based on the results and discussion of the research, it can be concluded that the rice field infrastructure improvement program is considered by the red chilli farmers to be the most influential of PT inalum's CSR (Corporate Social Responsibility) Program in Lubuk Cuik Village because the program is considered to be able to assist the farming business especially the road improvement to the area rice fields that are considered to be able to help the operations of red chili farmers and other farmers in Lubuk Cuik Village and irrigation canal improvement program which is considered to be very helpful in the irrigation process throughout the paddy fields in Lubuk Cuik Village because the trenches that were originally made of soil are now partially in the ground. cement which further facilitates the process of flowing water into the paddy fields. The production input assistance program in the form of red chili seeds, mulch, pesticides, and electric spraying is considered by some farmers to be ineffective because it can be said that the input assistance program is not evenly distributed throughout all caba farmers i red in Lubuk Cuik Village